A LA MEMORIA DE FRANCISCO SOLER GRIMA. EN EL CENTENARIO DE SU NACIMIENTO. - Guerra, Jorge Acevedo (Revista de Filosofía (00348236), 2024)
The article "IN MEMORY OF FRANCISCO SOLER GRIMA. ON THE CENTENARY OF HIS BIRTH" from the Philosophy Journal, written by Jorge Acevedo Guerra from the University of Chile, highlights the life and work of Francisco Soler Grima, a philosopher born in Spain in 1924. Soler was a professor at several Chilean universities and left a significant mark at the University of Chile. His philosophical approach was based on the idea that thinking is remembering and being grateful, influenced by Heidegger and Ortega. His legacy includes philosophical translations and commentaries.